Response restriction analysis in go/no-go procedure with compound stimuli with children with autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Studies that were successful in training conditional relations with children with autism through go/no-go with compound stimuli used a procedure called Response Restriction (RR). Since RR was used from the first trial, it was not possible to evaluate its effects on the participants' responding. This study conducted an analysis of previously published results in order to assess whether a pattern of respond to all compounds, common in children with autism, occurred with participants when RR was initially removed. Results showed that during RR removal, there was an abrupt increase in responses for most participants. After reintroduction and subsequent removal of RR, participants acquired conditional relations. Data from two new participants replicated these results. RR seems to be fundamental to establish a discriminated responding with this population with go/no-go with compound stimuli.